Structural variations in hyperbranched polymers prepared via thermal polycondensation of lysine and histidine and their effects on DNA delivery - Alazzo, Ali; Lovato, Tatiana; Collins, Hilary M.; Taresco, Vincenzo; Stolnik, Snjezana; Soliman, Mahmoud E.; Spriggs, Keith; Alexander, Cameron (Wiley, 2018)
The successful clinical translation of non-viral gene delivery systems has yet to be achieved due to the biological and technical obstacles to preparing a safe, potent and cost-effective vector. Hyper-branched polymers have emerged as promising candidates to address gene delivery barriers owing to their relatively simple synthesis and ease of modification compared to other polymers, which makes them more feasible for scale up and manufacturing. Here, we compare hyperbranched poly(amino acids) synthesised by co-polymerising histidine and lysine, with hyperbranched polylysine prepared using the well-known ‘ultra-facile’ thermal polycondensation route, to investigate the effects of histidine units on the structure and gene delivery applications of the resultant materials. The conditions of polymerisation were optimised to afford water-soluble hyperbranched polylysine-co-histidine of three different molar ratios with molecular masses varying from 13-30 kDa. Spectroscopic, rheological and thermal analysis indicated that the incorporation of histidine modulated the structure of hyperbranched polylysine to produce a more dendritic polymer with less flexible branches. Experiments to probe gene delivery to A549 cells indicated that all the new hyper-branched polymers were well-tolerated but, surprisingly, the co-polymers containing histidine were not more effective in transfecting a luciferase gene than hyper-branched poly(lysine)s synthesised as established literature comparators. We attribute the variations in gene delivery efficacy to the changes induced in polymer architecture by the branching points at histidine residues, and obtain structure-function information relating histidine content with polymer stiffness, pKa and ability to form stable polyplexes with DNA. The results are of significance to nanomedicine design as they indicate that addition of histidine as a co-monomer in the synthetic route to hyper-branched polymers changes not only the buffering capacity of the polymer but has significant effects on the overall structure, architecture and gene delivery efficacy.